Prevalence and Associated Factors of Metabolic Syndrome among Patients with Severe Mental Illness Attending a Tertiary Hospital in Southwest Uganda - Agaba, David Collins; Migisha, Richard; Namayanja, Rosemary; Katamba, Godfrey; Lugobe, Henry Mark; Aheisibwe, Hillary; Twesigomwe, Godfrey; Ashaba, Scholastic (BioMed Research International, 2019)
Globally, the prevalence of metabolic syndrome (MetS) and its components which are the major cardiovascular disease (CVD) risk factors, is higher among patients with severe mental illness (SMI) compared to the general population. 'is mainly due to the deleterious lifestyles characterized by physical inactivity, excessive alcohol consumption, smoking, and unhealthy diets common among patients with SMI as well as due to cardiometabolic effects of psychotropic medications. Despite these conditions being highly prevalent among patients with SMI, little attention is given to these conditions during routine reviews in the mental health clinics in most low-income countries including Uganda. 'e main objective of this study was to determine the prevalence and associated factors of MetS among patients with SMI at Mbarara Regional Referral Hospital (MRRH), a tertiary hospital in southwestern Uganda. Through a cross-sectional study at the mental health clinic of the hospital, we recruited 304 patients with SMI and evaluated them for MetS using the National Cholesterol Education Programme Adult Treatment Panel III (NCEP ATP III) criteria. We defined the prevalence of MetS as the proportion of patients meeting the NCEP ATP III criteria. We used logistic regression to evaluate associations between MetS and independent variables. We included a total of 302 (44.37% male, 55.63% female) patients with a diagnosis of SMI in the analysis. 'e prevalence of MetS was 23.51% (95% CI 18.84–28.71). At multivariable logistic regression, age >40 years and long duration of mental illness (>10 years) were significantly associated with MetS. 'e prevalence of MetS is high among patients with psychiatric disorders, and thus metabolic screening, especially among the high-risk groups, is critical.
Keywords: Metabolic Syndrome; Severe Mental Illness; Southwest Uganda